QSOX2‐Mediated Disulfide Bond Modification Enhances Tumor Stemness and Chemoresistance by Activating TSC2/mTOR/c‐Myc Feedback Loop in Esophageal Squamous Cell Carcinoma - Wo‐Ming Chen; Xiao‐Ping Zhang; Xiao Sun; Hai‐Cheng Liu; Yuan‐Yuan Yan; Xue Wei; Yu Liang; Yue Feng; Zhengjie Chen; Yongxu Jia; Chen Jiang; Qian Yan; et al. (Advanced Science)
Abstract Disulfide bond modification is critical in maintaining protein structure and activity, but its roles in regulating tumor stemness and chemoresistance remain underexplored. Here, Quiescin Sulfhydryl Oxidase 2 (QSOX2) is identified, a protein involved in disulfide bond formation, is highly expressed in esophageal squamous cell carcinoma (ESCC), and is associated with poor patient prognosis. Functional analyses demonstrated that QSOX2 overexpression markedly potentiated tumor stemness and further promoted chemoresistance, proliferation, and metastasis of ESCC cells. Mechanistically, QSOX2 enhances disulfide bond formation in TSC Complex Subunit 2 (TSC2), stabilizing TSC2‐Akt interactions, facilitating phosphorylation of TSC2 at the Ser939 by Akt, and further activating mTOR/4E‐BP1/c‐Myc signaling axis. Intriguingly, cancer‐associated fibroblasts‐secreted IGF‐1 upregulates QSOX2 expression via IGF1R/Akt/mTOR/c‐Myc pathway, establishing a positive feedback loop that sustains ESCC cell stemness. Targeting QSOX2 with Ebselen, in combination with mTOR inhibitor Rapamycin and chemotherapy, effectively downregulates c‐Myc expression and induces tumor dormancy in a mouse xenograft model. Therefore, the findings reveal that QSOX2‐mediated disulfide bond modification enhances tumor stemness by activating mTOR signaling, highlighting a promising therapeutic target in ESCC.